Implementation of Islamic School Culture-Based Curriculum Management in the Orientation of Educational Quality at SDI Athirah Makassar (Educational Management, 2022)
This study aims to describe and analyze the planning, organization, implementation and evaluation at SDI Athirah Makassar. This research approach uses a qualitative approach with an intrinsic case study design. The data collection process was carried out through observation techniques, interviews and document studies. The data and data sources were obtained by the school principal, SDI Athirah curriculum management team, vice principal, teachers, parents/guardians of students, and local community leaders. Then the data that has been collected is analyzed by means of qualitative analysis, namely the results of the research are arranged and translated in words to form sentences so that researchers can describe or explain the results of the research in depth according to the facts or conditions in the field. The results of this study indicate that in Islamic school culture-based curriculum management at SDI Athirah Makassar includes: (1) Planning with process stages (2) Organizing, divided into two things, related to the teacher's task and learning process (3) Implementation of MK SDI Athirah daily activities according to the sunnah of Rasulullah SAW, intracurricular activities, T3Q activities using the ummi method, English class, Manhaj Rabbani extracurricular activities. The implementation of MK SDI Athirah is an absorption of the QGDP program based on Islamic school culture which uses a triple curriculum called the AIHES curriculum. (4) Evaluation includes: process evaluation and results evaluation but sometimes also uses context, input, process, product evaluation models to make it more diverse.